2017
DOI: 10.2337/dc17-1306
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of ITCA 650, a Novel Drug-Device GLP-1 Receptor Agonist, in Type 2 Diabetes Uncontrolled With Oral Antidiabetes Drugs: The FREEDOM-1 Trial

Abstract: OBJECTIVEITCA 650 (exenatide in osmotic mini-pump) continuously delivers exenatide subcutaneously for 3-6 months. Two doses of ITCA 650 were compared with placebo in patients with uncontrolled type 2 diabetes. RESEARCH DESIGN AND METHODSThis 39-week, phase 3, double-blind, placebo-controlled trial randomized 460 patients aged 18-80 years with glycated hemoglobin (HbA 1c ) 7.5-10% [58-86 mmol/mol] 1:1:1 to placebo, ITCA 650 40 mg/day, or ITCA 650 60 mg/day. Primary end point was change in HbA 1c at 39 weeks. wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Semaglutide has two amino acid substitutions compared to native GLP-1 (Ala 8 by Aib 8 and Lys 34 by Arg 34 ), and similar to liraglutide, is attached at Lys 26 with a longer linker and a longer fatty acid chain of C18 instead of C16. 211 A Phase III open-label trial in type 2 diabetic patients with baseline A1c of 10.8% showed that after 39 weeks of treatment, a reduction of A1c of -2.8% was achieved. 205 The current FDA-approved semaglutide is administered via subcutaneous injection.…”
Section: Clinical Application Of Gip and Glp-1 In Obesity And Diabetesmentioning
confidence: 99%
“…Semaglutide has two amino acid substitutions compared to native GLP-1 (Ala 8 by Aib 8 and Lys 34 by Arg 34 ), and similar to liraglutide, is attached at Lys 26 with a longer linker and a longer fatty acid chain of C18 instead of C16. 211 A Phase III open-label trial in type 2 diabetic patients with baseline A1c of 10.8% showed that after 39 weeks of treatment, a reduction of A1c of -2.8% was achieved. 205 The current FDA-approved semaglutide is administered via subcutaneous injection.…”
Section: Clinical Application Of Gip and Glp-1 In Obesity And Diabetesmentioning
confidence: 99%
“…8,9 In a randomized, open-label, phase 2 study, patients with poorly controlled type 2 diabetes receiving metformin were treated using ITCA 650 delivering 20 lg of exenatide/day for 12 weeks followed by 60 lg/day for 12 weeks. These patients experienced significant reductions in HbA 1c of -1.4% and reductions in body weight of -3.1 kg during the initial 24-week treatment period, and these effects were maintained during a 24-week extension.…”
Section: Exenatidementioning
confidence: 99%
“…Mean weight losses of 2.3 kg and 3.0 kg were demonstrated in the ITCA 650 arms versus 1.0 kg loss with placebo (p < 0.015). At the end point, 37%, 44% and 9% of patients achieved an HbA 1c of 53 mmol/mol in the 40 μg/day, 60 μg/day and placebo groups, respectively (p < 0.001 versus placebo) …”
Section: Trials Of Safety and Efficacy In Diabetesmentioning
confidence: 98%
“…Two of the phase 3 efficacy and tolerability outcomes have recently been published. The FREEDOM‐1 trial was a double‐blinded randomised placebo controlled trial conducted over a 39‐week period. A total of 460 patients with established type 2 diabetes and HbA 1c between 58–86 mmol/mol were recruited from 126 sites in the USA and were randomised to receive ITCA 650 40 μg/day, ITCA 650 60 μg/day or identically placed mini pumps containing placebo.…”
Section: Trials Of Safety and Efficacy In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation